Mitochondrial Glycolysis in a Major Lineage of Eukaryotes. (30th July 2018) - Río Bártulos, Carolina; Rogers, Matthew B; Williams, Tom A; Gentekaki, Eleni; Brinkmann, Henner; Cerff, Rüdiger; Liaud, Marie-Françoise; Hehl, Adrian B; Yarlett, Nigel R; Gruber, Ansgar; Kroth, Peter G; van der Giezen, Mark
Abstract: The establishment of the mitochondrion is seen as a transformational step in the origin of eukaryotes. With the mitochondrion came bioenergetic freedom to explore novel evolutionary space leading to the eukaryotic radiation known today. The tight integration of the bacterial endosymbiont with its archaeal host was accompanied by a massive endosymbiotic gene transfer resulting in a small mitochondrial genome which is just a ghost of the original incoming bacterial genome. This endosymbiotic gene transfer resulted in the loss of many genes, both from the bacterial symbiont as well the archaeal host. Loss of genes encoding redundant functions resulted in a replacement of the bulk of the host's metabolism for those originating from the endosymbiont. Glycolysis is one such metabolic pathway in which the original archaeal enzymes have been replaced by bacterial enzymes from the endosymbiont. Glycolysis is a major catabolic pathway that provides cellular energy from the breakdown of glucose. The glycolytic pathway of eukaryotes appears to be bacterial in origin, and in well-studied model eukaryotes it takes place in the cytosol. In contrast, here we demonstrate that the latter stages of glycolysis take place in the mitochondria of stramenopiles, a diverse and ecologically important lineage of eukaryotes. Although our work is based on a limited sample of stramenopiles, it leaves open the possibility that the mitochondrial targeting of glycolytic enzymes in stramenopiles might represent the ancestral state for eukaryotes.